I feel it in my bones! An investigation into the mechanical and structural changes to bone as we age - McGivern, Hannah (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.Bone biomechanics is concerned with the study of the ailments and performance of our musculoskeletal system. Our knowledge of this field has been propelled forward by those in the automotive industry, who specialise in applied biomechanics and engineering. Their interest in this subject matter stems from the continual need to improve vehicle safety, but our skeletons also provide anthropological records of our lives, and can even act as a record of a criminal act. The aim of this research is to conduct a detailed assessment to examine the changes that occur to the structural and mechanical properties of the rib and clavicle bones, as we age. This multimethod approach will combine a non-invasive technique, micro-computed tomography (µ-CT), with multiple invasive methods including nanoindentation, dynamic mechanical analysis (DMA) and DSC-TGA. The proposed outcome of this research will be to use the resulting data to create a more comprehensive overview of the microarchitecture and mechanical behaviour of the rib and clavicle bones, which can then be used collaboratively with various disciplines. Understanding how these bones deteriorate with age will be particularly helpful for mitigating skeletal brittleness in some vulnerable groups like the elderly, by informing orthopaedic surgeons on the structure and condition of bone, which in turn could assist with the management of fractures through treatment and rehabilitation. Forensic anthropology, in parallel, will draw information to establish mechanisms of trauma, providing critical information for forensic investigations, as well as archaeological case studies that bear injuries, and in grasping the historical context for archaeological studies of past populations.
Keywords: 'Biomechanics'; 'Bone'; 'Age'; 'DSDS17 3MT'; 'DSDS17'; 'Biomechanics'